2019
DOI: 10.7717/peerj.6706
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence ofPseudomonas aeruginosaand multidrug resistantPseudomonas aeruginosain healthy captive ophidian

Abstract: Background Snakes are globally considered as pet animals, and millions of ophidians are bred in captivity. Pseudomonas aeruginosa is a ubiquitous Gram-negative bacterium that can act as an opportunistic pathogen of man and animals and is frequently present in the oral and cloacal microbiota of healthy ophidians. It can cause severe clinical diseases and often shows antibiotic resistance. The aim of this study was to evaluate the prevalence and antibiotic resistance profiles of P. aeruginosa isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…In contrast to the current study, some reports showed a low rate of resistance in the last three years, except for colistin, in which the same findings were described. 25,26 Also, the prevalence of KPC, ESBL-producing, and CRPA strains (as illustrated in Figure 1) was 25.74%, 24.75%, and 3.96%, respectively, which was in line with other studies. 27,28 However, other studies described the different abundance of P. aeruginosa isolates of KPC, ESBLproducer, and resistant to colistin.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to the current study, some reports showed a low rate of resistance in the last three years, except for colistin, in which the same findings were described. 25,26 Also, the prevalence of KPC, ESBL-producing, and CRPA strains (as illustrated in Figure 1) was 25.74%, 24.75%, and 3.96%, respectively, which was in line with other studies. 27,28 However, other studies described the different abundance of P. aeruginosa isolates of KPC, ESBLproducer, and resistant to colistin.…”
Section: Discussionsupporting
confidence: 89%
“…A similar scenario for a higher incidence of multidrug resistance (MDR) in hospital sewage than that in urban areas was observed in Coimbra, Portugal [ 24 ]. Most MDR bacteria, like MDRP, are opportunistic pathogens for humans and animals [ 25 ], and have been frequently reported in hospital outbreaks [ 26 , 27 ]. Consequently, hospitals are ecological niches for ARB and play a major role in the emergence and spread of these bacteria [ 11 ], especially for MDR species.…”
Section: Discussionmentioning
confidence: 99%
“…[64], Elizabethkingia meningoseptica [65], Enterobacter cloacae [64,65], Enterococcus pallens [77], Escherichia coli [51,64], Klebsiella oxytoca [49,65], K. pneumoniae [65], Klebsiella spp. [58], Leptospira grippotyphosa [61], Lysobacter pythonis [79], Moraxella osloensis [77], Morganella morganii [49,64], Mycoplasmosis [48], Proteus vulgaris [65], Providencia rettgeri [80], Pseudomonas aeruginosa [49,58,65,67], P. floureszens [65], P. japonica [77], Pseudomonas spp. [64], Salmonella Muenchen [65], Salmonella Paratyphi B [50,65], Salmonella spp.…”
Section: Bacteriamentioning
confidence: 99%